"Years ago": reconciliation and First Nations narratives of tuberculosis in the Canadian Prairie Provinces. Issue 4 (7th August 2016) - Komarnisky, Sara; Hackett, Paul; Abonyi, Sylvia; Heffernan, Courtney; Long, Richard
Abstract : For First Nations tuberculosis (TB) patients in the Prairie Provinces, the past matters. In this paper, we draw on the analysis of historical statements made by 20 First Nations interviewees with infectious TB to explore the function of talking about the past in relation to a current diagnosis of TB and the implications of historicity on contemporary TB prevention, programming and care. Despite interviewees not being asked directly about past contexts of TB treatment, they talked about historical topics such as the removal of First Nations TB patients from communities for treatment in distant sanatoria, painful and invasive surgical procedures once used to treat TB, and the attitudes that persist due to the ongoing failure to eliminate TB from First Nations communities. In these narratives, past experiences of TB treatment are intimately connected to present-day experiences and context. What happened 'years ago' profoundly affects the health and well-being of people diagnosed with TB today. Attempts to eliminate TB among First Nations peoples in Canada must also address its historical legacy. Understanding the contemporary effects of past TB treatment and mistreatment among First Nations peoples in the Prairie Provinces can also be seen as part of a larger project of truth and reconciliation in Canada, which involves both Indigenous and non-Indigenous Canadians.